1997
DOI: 10.1063/1.365318
|View full text |Cite
|
Sign up to set email alerts
|

Detonation waves in pentaerythritol tetranitrate

Abstract: Fabry–Perot laser interferometry was used to obtain nanosecond time resolved particle velocity histories of the free surfaces of tantalum discs accelerated by detonating pentaerythritol tetranitrate (PETN) charges and of the interfaces between PETN detonation products and lithium fluoride crystals. The experimental records were compared to particle velocity histories calculated using very finely zoned meshes of the exact dimensions with the DYNA2D hydrodynamic code. The duration of the PETN detonation reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 8 publications
2
42
0
Order By: Relevance
“…Fedorov et al [6] inferred reaction times of 90 -95 ns in seven experiments. Figure 4 shows the calculated PETN/LiF particle velocity histories for a PETN single crystal and a pressed PETN charge [5]. The initial interface [6].…”
Section: Comparisons Of Experimental and Calculational Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fedorov et al [6] inferred reaction times of 90 -95 ns in seven experiments. Figure 4 shows the calculated PETN/LiF particle velocity histories for a PETN single crystal and a pressed PETN charge [5]. The initial interface [6].…”
Section: Comparisons Of Experimental and Calculational Resultsmentioning
confidence: 99%
“…The reacting "hot spots" rapidly grow consuming the neighboring explosive particles and increasing the pressure and temperature as C-J detonation is approached [4]. "Super" detonation is not observed in porous solids, unless the initial density is extremely close to TMD [5]. Recently, Fedorov et al [6] reported nanosecond time resolved measurements of the interface particle velocity histories of detonating PETN and HMX single crystals with LiF windows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge is to compare microscopic simulation with experiment and coupling of simulation as well with recent results [3]. Different macroscopic kinetics and hotspot models are calibrated by experimental data and more precise simulations at microscopic to represent a pop-plot data [4,5] or initiation thresholds of shock-induced chemistry [6]. However, there is still a great debate of direct hotspot simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Laser light reflected from the mirror is Doppler shifted when the velocity changes and an interferometer transduces this into particle velocity of the interface vs. time. Several studies have used this technique in various interferometer setups (ORVIS and Fabry-Perot) to estimate reaction zones in various explosives (3)(4)(5). Time resolution can range from 10 ns down to subnanosecond, depending on the interferometer and the recording technique.…”
Section: Introductionmentioning
confidence: 99%